Synthesis of esters derived from 2,3,4,6-tetra-O-acetyl-1-[4-(2-hydroxyethyl)-1H-1,2,3-triazol-1-yl]-β-D-glucopyranose - Pinto, Tiago Alexandre Dinis; Silva, Marilia; Cunha, Silvia; Oliveira-Campos, Ana Maria Ferreira; Rodrigues, Ligia Marona; Hrdina, Radim; Esteves, Ana Paula (European Journal of Chemistry, 2013)
2,3,4,6-Tetra-o-acetyl-1-[4-(2-hydroxyethyl)-1H-1,2,3-triazol-1-yl]-β-D-glucopyranose was prepared and reacted with several acids, either commercially available or prepared. These included, aliphatic or aromatic acids (phenylacetic acid derivatives, benzoic derivatives), palmitic acid and the protected amino acids N-(benzyloxycarbonyl)glycine and N-(tert-butyloxycarbonyl)-phenylalanine. Two other acids, 2-(3-bromopropoxy)benzoic acid and 2-(5-bromopentoxy)benzoic acid (analogues of salicylic acid were synthesized), whose preparation is also described in this work. The esterification was performed either with N,N'-dicyclohexylcarbodiimide (DCC)/4-dimethylaminopyridine (DMAP) or by reacting the acyl chlorides with the alcohol in the presence of triethylamine. The products were isolated in fair yields and fully characterized by the usual analytical techniques.